Peran Organisasi Perempuan dalam Penguatan Social Capital Melawan Pandemi Covid-19 (Studi pada Gerakan Kampanye Sosial Persit Kartika Chandra Kirana XXXIX Kabupaten Pati Jawa Tengah) - Dewi Erowati; Kuncoro Bayu Prasetyo; Sri Astuty; Tutting Anggraeni (Universitas Padjadjaran, 2020)
The Covid-19 pandemic has spread globally. In Indonesia, when the pandemic destroys the health system and global economy, social capital arrives as an alternative to sustain community resilience. This research aims to 1) describe a social capital within the community and how it is being campaigned and strengthened within the community by the actors in the community itself amidts their effort to overcome the Covid-19 pandemic; and 2) to describe community’s response towards the social capital campaign.The study was conducted using qualitative methods. Observation was conducted towards various activism by Persit KCK XXXIX Pati; a women’s organizations, in particular their activities in social campaign against Covid-19 pandemic. The results of this research suggest that social capital can be an alternative for community survival when economis capital destroyed. Solidarity and mutual assistance among community members without considering the financial benefits is crucial in a crisis situation of the Covid-19 pandemic. Persit Kartika Chandra Kirana Branch XXXIX Pati through its various voluntary and non-profit activities has shown itself as one of the driving forces for the growth and revitalization of social capital within the community, especially through the networks that they structurally or non-structurally owned.